TECHNOLOGIES AND SUSTAINABLE DEVELOPMENT: THE CULTURAL LANDSCAPES OF THEMEDITERRANEAN - Antonio, P. D.; Romano, Francesca Vera; Scalcione, V. N.; Antonio, C. D. (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2020)
The research aims to highlight how Matera and Pompeii, both UNESCO sites are united by a thousand-year-old history always alive, a heritage made of archaeological remains, paintings, frescoes and intangible goods. Henry Vollam Morton in his book "A traveler in Southern Italy" tells of his visit to Matera in the 60’s, when the Sassi had been abandoned and the population moved for the most part to new neighborhoods, and the city appears to his eyes as "an incredible Pompeii” suspended between past and future, once lived and then abandoned. Today both realities live again thanks to people and institutions who believed in the possibility to restore their life through technology and to resurface enclosed treasures still to be discovered. Pompeii, an ancient Roman colony, although it seems for its history a crystallized city, is always alive and moving thanks to the continuous discoveries that make it one of the most visited destinations with an exponential growth of tourists. Matera was in the last century with the agricultural neighborhood and it is now because like other cities it is into the phase of experimenting with ultra-fast 5g telephony. The 5G experiment has shown that the use of satellite technologies can be of great help to the management and sustainability of cultural landscapes because of support to the development of culture and creativity to the management of visitors, the organization of the tourist destination and the use of cultural heritage and also it enhance and preserves agricultural landscapes and productions, as an expression of the relationship of the community with the natural space.